MAKRIFAT DALAM AL-QUR’AN Study atas Tafsir Al-Azhar - Nurbaety Mustahele (Institut PTIQ Jakarta, 2019)
The conclusion of this thesis is to create integrity and honesty for modern humans, it can be through a means of understanding that is to know God Almighty and always feel His presence. The achievement (stage) of makri-fat which is the existence of Allah SWT, does not occur suddenly without going through a long and winding process, because the meaning of Allah SWT is only possible with an effort that is truly serious in claiming it. According to Hamka, the light of Divine guidance bounces into the light of the heart which has escaped temptation. In addition to such piety, there is wasila, namely the ways and ways to get closer to God, namely to increase the acts of worship, to do good, to uphold high mind, to be compassionate towards fellow human beings. Increasing a lot of good deeds, it will get closer to the pleasure of God. Wasilah is the effort of each person’s charity with his own business